Evaluation of durum wheat (Triticum turgidum) genotypes for genetic variability, heritability, genetic advance and correlation studies - Gerema, Geleta (Journal of Agriculture and Natural Resources, 2020)
The present investigation was undertaken to study the genetic variability, heritability and correlation coefficient analysis for 7 metric traits in 12 durum wheat genotypes at western Oromia during 2015-2018. Significant genotypic differences were observed for the majority traits studied, indicates considerable amount of variation among genotypes for each character. The estimates of genotypic coefficient of variation (GCV) and phenotypic coefficient of variation (PCV) were high for kernels per spikelet, thousand kernels weight, and number of kernels per spike and grain yield. The remaining traits were ranged from low to moderate estimates. High heritability estimates were recorded for the majority traits studied. The estimated broad – sense heritability (h2) has ranged from 31.6% for maturity to 80.8% for grain yield. High genetic advance combined with high heritability was recorded for plant height, thousand kernel weight, kernels per spike and grain yield, indicates that most likely selection based on phenotype of genotypes could be effective to improve these characters. Grain yield was positively and significantly correlated with spike length, kernels per spike and thousand kernels weight both at genotypic and phenotypic levels. The strong correlation of grain yield with the mentioned traits showed that grain yield could be indirectly improved through improving these traits. This information might be used in the genetics and breeding programmes for improvement of durum wheat.